Risk management in e-business application development / Ahmad Faizul Haraza A. Razap - A. Razap, Ahmad Faizul Haraza (Faculty of Computer and Mathematical Sciences, 2007)
Software development projects become more challenging as the size and complexity of the systems being developed is growing. However, the capability to build software has not increased proportionately to demand and shortfalls in regard are a growing concern. Software projects are exposed to various risks where risk is understood as a possibility of loss, damage or disadvantages. The risk is related to the whole project is to deliver in time and within the budget constrains, a product that meets client needs and expectation. A project without risk management will face problem only after the risks came to the siirface as a material fact. So, this will increase time and cost of project Risk normally refers to something that is "uncertain" and that uncertainty normally carries a loss or adverse effect. . From the formal interview with the IT company, the researcher have gain some risks and problems faced by the respondent in software development life cycle. From the literature review, researcher has merged the result from the interview with literature review. Risk management describes the techniques and guidelines that identify, analyze and tackle software risks. Software risks are illustrated as endanger a successful development leading to wrong or inadequate software operation, software rework, implementation difficulty, delay or uncertainty. To objective of this project is the risk in E-Business application development. After all the study done bye the researcher, the final product of this research is to develop an effective tool for collaborative risk management.